Two Rebel Roads to Power: Explaining Variation in the Transition from Genocidal Violence to Rebel Governance in Contemporary Rwanda and Burundi. - Twagiramungu, Noel. (2017)
Abstract: Rwanda and Burundi are often considered twin countries, exhibiting almost identical historical and linguistic heritage, cultural norms and practices, and social and political structures. Equally landlocked, poor in natural resources, and aid-dependent, the two former Belgian colonial territories have since the 1990s emerged from comparable instances of genocidal violence and rebel-led transitions. Yet these transitions occurred in radically different ways. The Tutsi-dominated Rwandan Patriotic Front (RPF) came to power through a military victory and established a strong, donor-darling state with an exaggerated presence in the international arena. Burundi's Hutu-dominated Conseil National pour la Défense de la Démocratie-Forces de Défense de la Démocratie, (CNDD-FDD) forced a Tutsi-controlled army to negotiate a power-sharing arrangement and now presides over a divided government with little influence beyond its national borders. This dissertation argues that these divergent transitions are not simply an outcome of contingent and idiosyncratic factors such as war, genocide, conflict endgame, external influences or individual leaders. Instead, the differences are better understood as the continuation of longstanding political patterns. The argument rests on four empirical findings. First, the coming into being of Rwanda and Burundi was the result of complex processual developments of political negotiation rather than instantaneous structures created whole each under one founding father. Nevertheless, the origins of the current patterns of governance can be traced back to the early political foundations of each state. One of Rwanda's foundational monarchs, Ruganzu Ndori, came to power by force in a time of extreme turmoil; he introduced two innovative political tools -- a strong army and a clientele system known as ubuhake -- which allowed the central court increasing control over its expanding territory. Burundi's founder, Ntare Rushatsi, rose to prominence in peacetime, by gradually extending his influence over complex webs of power-holders; the resultant royal structures were based on a delicate web of relations among several semi-autonomous princes. As Ruganzu's successors consolidated power, by the mid-eighteenth century Rwanda came to be a highly militarized and fairly centralized kingdom. By contrast, Burundi retained its features of a confederation among regional authorities. Second, the foundational political styles responded to the challenges of their times, adapting to shifting dynamics; neither colonial domination nor the post-independence rise of military rule, democratization processes or rebel governance reversed the age-old trends. Third, this dissertation explains why, upon assuming power, new leaders tend to reproduce the same governance systems they once vowed to eradicate. I argue that political entrepreneurs, including rebellions, find themselves obliged to preserve institutions and practices that resonate most with the society as a whole. They do so both in their individual efforts to minimize the risks of uncertainties (as instrumental-rational theorists may correctly suggest), and because, having been socialized into these norms and practices, they have had to internalize and work within them to achieve success. Fourth, the prevailing patterns of governance--centralization in Rwanda, fragmentation in Burundi--, while self-reinforcing, are neither linear nor deterministic. The analysis examines five pairs of variables whose interactions and trade-offs shape each society's responses to ever-changing challenges and opportunities: relations between past and present; center and periphery; agency and structure; elites and multiple lay groupings; internal and external factors. Put together, the findings suggest that good understanding of the core norms and practices likely to shape the boundaries of choices and margins of maneuver available to individual and institutional actors is key for designing balanced, well-informed, context-sensitive and change-oriented policies.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisors: Peter Uvin, and Eileen Babbitt.; Committee: Jens Meierhenrich.; Keywords: International relations, Peace studies, and Sub Saharan Africa studies.